Hemodynamic Performance of Endovascular Valves as Valve-in-Valve in Small Stented Bioprosthesis - Kuehnel, Ralf-Uwe; Hartrumpf, Martin; Erb, Michael; Albes, Johannes M. (The Thoracic and Cardiovascular Surgeon, 2017)
Background Endovascular valve in stented biological valve implantation (valve-in-valve transcatheter aortic valve implantation [TAVI ViV]) is increasingly becoming a valid option for bioprosthesis degeneration. TAVI implantation in small stented biological valves below 23 mm is controversially discussed. Reduced opening area and high gradients are typical objections against this procedure in cases of small bioprosthesis. Systematic studies about the hemodynamic performance of endovascular valves in small stented bioprosthesis, however, do not exist.Methods Stented biological valves of 21 mm size were analyzed in a pulse duplicator (cardiac output 4.9 L/min). Edwards Perimount Magna (EP; Edwards Lifesciences, Irvine, California, United States), Medtronic Mosaic (MM; Medtronic Inc., Minneapolis, Minnesota, United States), and Sorin Mitroflow (SM; Milan, Italy) were investigated (three valves, each type). Mean transvalvular gradients were measured before and after implantation of Edwards Sapien 23 mm (SAP) as ViV.Results There were no marked differences of mean transvalvular gradients before and after ViV (EP21: 12.3 mm Hg; EP21 + SAP: 11.1 mm Hg; SM21: 13.5 mm Hg; SM21 + SAP: 14.9 mm Hg; MM21: 21.4 mm Hg; MM21 + SAP: 15.1 mm Hg). MM valves fabricated from porcine cusps showed higher initial gradients in contrast to valves constructed with pericardium (EP and SM). After ViV, however, this difference was reduced.Conclusion This in vitro study shows that hemodynamic performance of endovascular valves as ViV in small bioprosthesis does not differ significantly from the performance of the initial implanted prosthesis. Hemodynamic performance of porcine cusp valves could even be optimized. It can thus be speculated that TAVI ViV also offers a reasonable option for patients with typical stented bioprosthetic degeneration to substantially prolong adequate function with one initial surgical and one consecutive interventional procedure even in small valves.
Keywords: endovascular procedures; aortic valve replacement; minimally invasive surgery; cardiac output